2014
DOI: 10.1007/s00436-014-4135-y
|View full text |Cite
|
Sign up to set email alerts
|

Parascaris univalens—a victim of large-scale misidentification?

Abstract: The equine ascarid parasite Parascaris equorum is well known as a ubiquitous parasite infecting foals. A sibling species, Parascaris univalens, was first described over 130 years ago, but very little attention has been given to its existence and possible implications for anthelmintic resistance, clinical disease, or host age spectrum. P. univalens only possesses one germ line chromosome pair as opposed to two for P. equorum, but the two species are otherwise considered morphologically identical. For the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 19 publications
0
34
0
1
Order By: Relevance
“…One abattoir-based prevalence survey conducted in Italy in the 1970s indicated an overwhelming dominance of P. univalens among more than 2000 investigated specimens (Bullini et al 1978). A recent karyotype investigation of worm specimens and ascarid eggs obtained from faecal samples collected from foals in Central Kentucky identified only P. univalens (Nielsen et al 2014a). Further, a recent study of the population structure among about 200 equine ascarid specimens collected in Sweden, Norway, Germany, Iceland, Brazil and USA concluded that all specimens were genetically homogenous (Tyden et al 2013), and one of the US isolates collected for this study was later identified to be P. univalens.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…One abattoir-based prevalence survey conducted in Italy in the 1970s indicated an overwhelming dominance of P. univalens among more than 2000 investigated specimens (Bullini et al 1978). A recent karyotype investigation of worm specimens and ascarid eggs obtained from faecal samples collected from foals in Central Kentucky identified only P. univalens (Nielsen et al 2014a). Further, a recent study of the population structure among about 200 equine ascarid specimens collected in Sweden, Norway, Germany, Iceland, Brazil and USA concluded that all specimens were genetically homogenous (Tyden et al 2013), and one of the US isolates collected for this study was later identified to be P. univalens.…”
Section: Introductionmentioning
confidence: 62%
“…A recent karyotype investigation of worm specimens and ascarid eggs obtained from faecal samples collected from foals in Central Kentucky identified only P. univalens (Nielsen et al . ). Further, a recent study of the population structure among about 200 equine ascarid specimens collected in Sweden, Norway, Germany, Iceland, Brazil and USA concluded that all specimens were genetically homogenous (Tyden et al .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent work suggests that the predominant equine ascarid species is Parascaris univalens and not Parascaris equorum, as commonly assumed (Nielsen et al . ). Even foals of the youngest age group are likely to ingest ascarid eggs as they suckle the mare and explore their immediate environs.…”
Section: Birth To 2 Monthsmentioning
confidence: 97%
“…The ascarid is most often found in the small intestine of foals and less commonly in weanlings and young horses. Slow growth, weight loss, cough and colic are all signs of potential massive gastrointestinal infection (Reinemeyer 2009;Nielsen et al 2014). Cyathostomins are found in the large intestines of horses; aggregation of the developmental stages in the mucosa of the large intestine can lead to clinically apparent disease which manifests itself as diarrhoea, hypoproteinaemia, subcutaneous oedema and metabolic acidosis (Lyons et al 2000).…”
mentioning
confidence: 99%